Pengaruh Intensitas Berita Brigadir J di Tiktok Terhadap Citra Polri Dimata Mahasiswa - Rahayu, Nabilla Dwi; Yuniarti, Renty (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
Exposure is an activity of reading, viewing and listening to messages from various media that have meaning from these messages, this happens to every individual or group. In this study, it discusses the Intensity of Brigadier J on Tiktok on the Image of the National Police on Students’ point of view who have a problem formulation to find out how much influence the Intensity of Brigadier J on Tiktok has on the Image of the National Police on Students’ point of view with the aim of knowing the effect of the Intensity of Brigadier J on Tiktok on the Image of the National Police on Students’ point of view. This journal belongs to one of the major themes, namely: Human-Machine Communications. Using the positivism paradigm with an exploratory quantitative approach method and data collection non probability techniques using accidental sampling type by distributing questionnaires to STIKOM InterStudi Students Class Batch 2019-2022. The sample used was seventy-five respondents. Data was collected via Google Form with a five-point Likert scale measurement. Data processing techniques using simple Linear Analysis Techniques with IBM SPSS V.29 software to test validity and reliability, F test, and Individual significant test (t test). The results of this study obtained a t-test result of zero point eight hundred three which is greater than zero point zero five where the regression coefficient is positive, which means it is valid. So it means that Ha is accepted and Ho is rejected because there is an influence of the Intensity variable (X) on the Image variable (Y). Then the output results obtained were forty point eight percent which stated that the results of the study were in the moderate/moderate category of influence while the remaining fifty-nine point two percent was influenced by other variables that was not examined in this research.